Changes in the Time Spent on Physical Activities of University Students Before and During the COVID-19 Outbreak (Papers in Arts and Humanities, 2022)
In Spring 2020 in many countries various restrictions were implemented to try to prevent the spread of the coronavirus disease. Among these Covid-19 measures lockdowns had a big impact on people’s lives. The opportunities for physical activities have been reduced since people had to manage working or learning from their homes. This research paper focuses on the changes of the time spent on physical activities of university students. Our intention is to reveal the enhancing factors for a positive and negative change in the frequency of physical activity. The analyses are based on the data for the University of Szeged of the COVID-19 International Student Well-Being Study elaborated and conducted by the University of Antwerp in Spring 2020. The online questionnaire, filled out by 1808 students from the University of Szeged, included two questions concerning the frequency of doing moderate and vigorous physical activity before and during the COVID-19 outbreak. The analyses of the changes in the time spent on physical activities focuses on the associations with socio-demographic factors and health status. Results indicate that increase in physical activity was typical for women, students in a relationship, and those who moved from their place of residence. A decline in physical activity has been found to be characteristic for younger students. Having a health risk condition turned out to have no effect on changes in physical activity, but satisfaction with health is associated with the increase or decline in physical activity.
Keywords: physical activity; COVID-19; lockdown; university students; health status